Use of modelling to compare the impact of roadside drying of Pinus radiata D.Don logs and logging residues on delivered costs using high capacity trucks in Australia. (April 2021) - Strandgard, Martin; Acuna, Mauricio; Turner, Paul; Mirowski, Luke
Abstract: Forest biofuel delivered costs are generally uncompetitive with fossil fuels. Drying forest biofuel can potentially reduce delivered costs through weight reductions and net calorific value increases. The study examined the impact of roadside drying (RD) and use of high-volumetric capacity trucks on delivered costs of Pinus radiata pulp-logs and logging residue (LR) chips supplying a gasification plant. Five truck configurations: 6-axle semi-trailers; 9-axle B-doubles; proposed high-volumetric (HV) capacity versions of these trucks (HV semi-trailers and B-doubles); and 11-axle pocket road trains (PRT), were investigated across six supply areas using a forest biomass supply chain tool. Without RD all truck configurations were weight limited transporting logs, and all (except HV semi-trailers and B-doubles) were volume limited transporting LR chips. Post-RD all truck configurations were volume limited transporting logs or LR chips, (except HV B-doubles transporting logs). RD considerably reduced delivered costs: PRT (22%), B-doubles (24%), semi-trailers (25%) for logs and PRT (28%), B-doubles (29%), semi-trailers (30%) for LR chips. Delivered cost differences between truck configurations reflected transport cost differences. Without RD, truck trips transporting log were directly related to truck weight capacity. Additional volumetric capacity enabled HV semi-trailers and B-doubles to transport 6% and 4% more LR chips than standard versions, respectively, with equivalent truck trip reductions. RD weight reductions were: logs (33%); LR chips (53%), with consequent reductions in truck trips. PRTs required fewest truck trips to transport logs and LR chips without RD and the second fewest for logs post-RD due to their high weight and volumetric capacities. Highlights: Delivered log and residue costs were examined using a supply chain modelling tool. Delivered cost reductions from roadside drying were considerable. Cost reductions resulted from drying weight losses and net calorific value gains. High-volume trucks combined with roadside drying produced the greatest gains.